2022
DOI: 10.1093/ve/veac089
|View full text |Cite
|
Sign up to set email alerts
|

Global estimates of the fitness advantage of SARS-CoV-2 variant Omicron

Abstract: New variants of SARS-CoV-2 show remarkable heterogeneity in their relative fitness over both time and space. In this paper we extend the tools available for estimating the selection strength for new SARS-CoV-2 variants to a hierarchical, mixed-effects, renewal equation model. This formulation allows us to estimate selection effects at the global level while incorporating both measured and unmeasured heterogeneity among countries. Applying this model to the spread of Omicron in forty countries, we find evidence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
3
4
0
Order By: Relevance
“…The most recent COVID-19 wave in Amazonas, however, displayed some unique features. The Omicron BA.1 wave displayed a higher peak of SARS-CoV-2 cases and shorter duration than previous waves, as observed in other Western countries 18,48,49 . We speculate that the weak mitigation measures implemented in Amazonas during the dissemination of Omicron BA.1 may have resulted in a high and sharp peak with a rapid decline, while the curve of previous variants may have been "flattened" and prolonged by more stringent control measures implemented earlier (Fig.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The most recent COVID-19 wave in Amazonas, however, displayed some unique features. The Omicron BA.1 wave displayed a higher peak of SARS-CoV-2 cases and shorter duration than previous waves, as observed in other Western countries 18,48,49 . We speculate that the weak mitigation measures implemented in Amazonas during the dissemination of Omicron BA.1 may have resulted in a high and sharp peak with a rapid decline, while the curve of previous variants may have been "flattened" and prolonged by more stringent control measures implemented earlier (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Delta in Amazonas (~3) was roughly comparable to that estimated in other settings with different infection and vaccination histories like South Africa, Denmark, the UK, the United States of America, and India (~2-5) 27,[29][30][31] . The Omicron BA.1 outbreak in Amazonas also had a similar duration from the onset of case growth to their peaks (~30 days) than that observed in other populations with different immune landscapes 18,48,49 . These data support that immunologicalrelated covariates alone could not explain heterogeneity in Omicron's fitness across countries 5,49 .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We found that Omicron variants were responsible for approximately 404 million (95% CrI = 221-617 million) infections across the US from December 2021 to March 2023, including approximately 169 million during the BA.1* wave. The transmission dynamics of variants differed markedly: BA.1* emerged as a genetically distinct (3,(23)(24)(25) variant which caused large rapid epidemics, especially in states with a higher degree of social vulnerability. Subsequent Omicron variants, while able to both co-circulate and eventually outcompete extant strains, spread at lower levels and often for longer durations, exhibiting much weaker association with social vulnerability measures than the BA.1* variant.…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 genome shows signs of continued adaptation to human immunity after transmission from the non-human reservoir, much like other zoonotic RNA viruses Middle Eastern Respiratory Syndome Coronavirus (MERS-CoV) and influenza [ 29 , 31 ]. Furthermore, the relative fitness of different SARS-CoV-2 variants is heterogenous across different geographic regions, likely reflecting a changing immunological landscape influenced by genetics, as well as infection and vaccination rates [ 30 , 32 ].…”
Section: Selection Is An Indicator Of Viral Evolutionmentioning
confidence: 99%